2019
DOI: 10.1002/pssb.201900161
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Schottky Barrier of Graphene/WS2 Heterostructure With Vertical Electric Field and Biaxial Strain

Abstract: Graphene has been widely used in many applications, such as sensors, fieldeffect transistors, and integrated circuits due to its high strength and excellent electrical and thermal conductivity. Its lack of a band gap, however, means that applications in some fields are limited. In this paper, using first principles calculations based on the density functional theory method, the electronic properties of graphene/WS 2 heterostructures under electric field and in-plane biaxial strain are investigated. It is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…First, the E b for the MoS 2 (WS 2 )/BSe heterostructures is −217.20 (−295.00) meV, which is far less than that of the prepared graphene/WS 2 compound (−31.95 meV), [ 36 ] indicating a promising prospect to synthesis the XS 2 /BSe heterostructures experimentally. Next, the equilibrium distances of the MoS 2 /BSe, and WS 2 /BSe heterostructures are measured as 3.25 and 3.20 Å, respectively, which are very close to that of other existent TMDs‐based vdW heterostructures, such as graphene/WS 2 (3.32 Å), [ 36 ] and graphene/MoS 2 (3.40 Å). [ 37 ] This indicates the possibility of the existence of XS 2 /BSe vdW heterostructures.…”
Section: Resultsmentioning
confidence: 99%
“…First, the E b for the MoS 2 (WS 2 )/BSe heterostructures is −217.20 (−295.00) meV, which is far less than that of the prepared graphene/WS 2 compound (−31.95 meV), [ 36 ] indicating a promising prospect to synthesis the XS 2 /BSe heterostructures experimentally. Next, the equilibrium distances of the MoS 2 /BSe, and WS 2 /BSe heterostructures are measured as 3.25 and 3.20 Å, respectively, which are very close to that of other existent TMDs‐based vdW heterostructures, such as graphene/WS 2 (3.32 Å), [ 36 ] and graphene/MoS 2 (3.40 Å). [ 37 ] This indicates the possibility of the existence of XS 2 /BSe vdW heterostructures.…”
Section: Resultsmentioning
confidence: 99%
“…These layered materials show a decrease in interlayer spacing when external pressure is applied, reducing the contact resistance amongst the nanoflakes, thereby enabling interlayer electron tunneling. The resistance created due to the formation of a heterojunction at the interface decreases with applied pressure due to SBH lowering (Φ' SB ) [52]. Figure 6 shows in graphical form the effect of external stimuli (pressure, strain) on the TMD/MXene layers and the tunneling phenomena that occur.…”
Section: Sensing Mechanisms 331 Pressure and Strain Sensing Mechanismmentioning
confidence: 99%
“…Φ Bp = 0.65eV for MoSe 2 /Gr, Φ Bn = 0.39eV and Φ Bp = 1.13eV for WS 2 /Gr, and Φ Bn = 1.00eV and Φ Bp = 0.61eV for WSe 2 /Gr, respectively. Therefore, MoS 2 /Gr, MoSe 2 /Gr, WS 2 /Gr and WSe 2 /Gr are the n-type, p-type, n-type and p-type Schottky contacts, respectively [47,49,51].…”
Section: A Band Structuresmentioning
confidence: 99%
“…The MX 2 /Gr are the type-I van der Waals heterostructures. The electronic properties of MoS 2 /Gr [33,[42][43][44][45], MoSe 2 /Gr [28,[46][47][48], WS 2 /Gr [29,49] and WSe 2 /Gr [50][51][52] have been revealed that MX 2 /Gr van der Waals heterostructures are favourable for optoelectronic applications and field-effect transistors. In this paper, we theoretically investigate the optical properties of MX 2 /Gr (M=Mo,W; X=S,Se) heterostructures.…”
Section: Introductionmentioning
confidence: 99%